Optimalisasi Struktur Organisasi dalam Bisnis Herava untuk Mengatasi Hambatan pada SDM yang Terbatas - Sarfani, Desta; Siti Julfa Fitriyah; Khalisa, Sahna; Siskawati, Isna (Jurnal STIA Bengkulu, 2026)
This study aims to optimize the organizational structure of Herava, a herbal beverage brand founded by Generation Z students, in order to overcome the constraints of limited human resources within the team. The research focuses on improving the organizational structure, defining job descriptions, and refining the chain of command to enhance team coordination and work efficiency. A qualitative descriptive approach was used, with data collected through observation, interviews, and participatory group discussions. The results show that with a more organized structure and clear division of tasks, team performance can improve even with limited human resources. These findings provide valuable insights for innovation-based MSMEs, especially those managed by students, in maximizing resource management to support sustainable business development.